The uses of bacteria in cancer therapy - Saha, Shimul; Mollick, Simi; Zaman, Shaila (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.